In vitro and in vivo antimalarial activity and cytotoxicity of extracts, fractions and a substance isolated from the Amazonian plant Tachia grandiflora (Gentianaceae) - Luiz Francisco Rocha e Silva; Emerson Silva Lima; Marne Carvalho de Vasconcellos; Ellen Suzany Pereira Aranha; David Siqueira Costa; Elba Vieira Mustafa; Sabrina Kelly Reis de Morais; Maria das Gracas Costa Alecrim; Sergio Massayoshi Nunomura; Lena Struwe; Valter Ferreira de Andrade-Neto; Adrian Martin Pohlit (Memorias do Instituto Oswaldo Cruz, 2013)
Tachia sp. are used as antimalarials in the Amazon Region and in vivo antimalarial activity of a Tachia sp. has been previously reported. Tachia grandiflora Maguire and Weaver is an Amazonian antimalarial plant and herein its cytotoxicity and antimalarial activity were investigated. Spectral analysis of the tetraoxygenated xanthone decussatin and the iridoid aglyone amplexine isolated, respectively, from the chloroform fractions of root methanol and leaf ethanol extracts was performed. In vitro inhibition of the growth of Plasmodium falciparum Welch was evaluated using optical microscopy on blood smears. Crude extracts of leaves and roots were inactive in vitro. However, chloroform fractions of the root and leaf extracts [half-maximal inhibitory concentration (IC50) = 10.5 and 35.8 µg/mL, respectively] and amplexine (IC50= 7.1 µg/mL) were active in vitro. Extracts and fractions were not toxic to type MRC-5 human fibroblasts (IC50> 50 µg/mL). Water extracts of the roots of T. grandiflora administered by mouth were the most active extracts in the Peters 4-day suppression test in Plasmodium berghei-infected mice. At 500 mg/kg/day, these extracts exhibited 45-59% inhibition five to seven days after infection. T. grandiflora infusions, fractions and isolated substance have potential as antimalarials.